Virtual Reality Wisata Pesisir Pantai Timur Kabupaten Minahasa: Virtual Reality Coastal Tourism on the East Coast of Minahasa Regency - Clayf Rantung; Nancy Tuturoong; Jimmy Robot (Universitas Sam Ratulangi, 2024)
Abstract — The tourism sector has been skyrocketing thanks to the information technology that keeps innovating. With blazing speed and widely available internet connection, a tourist nowadays can easily decide where they will spend their time on holiday. The Minahasa East Coast has been very popular with the people of North Sulawesi because of the white sand beaches. Unfortunately, the North Sulawesi has not been actively promoting the tourism section. This research aims to design and build a tourism application to highlight the tourism potentials that span across the Minahasa East Coast. The virtual reality application “Explore: Tondano Pante” has been successfully developed with the Multimedia Development Life Cycle (MDLC) method that consists of Concept, Design, Material Collecting, Assembly, Testing and Distribution. Key words— Tourism; Virtual Reality; Virtual Tour; Pano2VR; Photogrammetry Abstrak — Sektor pariwisata akhir-akhir ini berkembang dengan pesat berkat kemajuan teknologi informasi yang terus memberikan inovasi tanpa henti. Dengan akses internet yang tersedia secara luas saat ini para wisatawan akan sangat mudah untuk memutuskan dimana mereka akan menghabiskan waktu untuk berlibur. Pantai timur Minahasa sendiri sudah cukup dikenal oleh masyarakat Sulawesi Utara karena keindahan pasir putihnya, namun sayangnya upaya dari pemerintah untuk mempromosikan pariwisata di bagian pantai timur Minahasa masih sangat minim. Tujuan dari penelitian ini yaitu untuk merancang dan membangun sebuah aplikasi wisata yang bertujuan untuk meng-highlight potensi-potensi pariwisata yang ada di pesisir pantai timur Minahasa. Aplikasi Virtual Reality Wisata Pesisir Pantai Timur Kabupaten Minahasa “Explore: Tondano Pante” kemudian telah berhasil dikembangkan menggunakan metode Multimedia Development Life Cycle (MDLC) yang terdiri dari 6 tahapan, yaitu Concept, Design, Material Collecting, Assembly, Testing dan Distribution. Kata kunci — Pariwisata; Virtual Reality; Virtual Tour; Pano2VR; Photogrammetry